Simultaneous Quantification Method of Flavonoids in Jeju Native Citrus from Different Harvest Times Using a High-Performance Liquid Chromatography–Diode Array Detector (HPLC–DAD) - Hyeon, Hyejin; Hyun, Ho Bong; Kim, Sung Chun; Go, Boram; Yoon, Seon-A; Jung, Yong-Hwan; Ham, Young-Min (Separations, 2023)
In Jeju-native Citrus, flavonoids are the main contributors to the various types of biological activity, such as antioxidant, antitumor, and anti-inflammatory activity. Thus, we developed simultaneous quantification methods for the analysis of ten bioactive flavonoids in Jeju Citrus fruits (Dangyuja, Gamja, Jigak, Sadugam, and Soyuja) harvested at six different time points using a high-performance liquid chromatography–diode array detector (HPLC-DAD). Separation was performed using a flow rate of 0.8 mL/min, a column temperature of 40 °C, a mobile phase buffer of 0.5% acetic acid, and a detection wavelength of 278 nm. The established analytical method showed good linearity (R2 ≥ 0.9997), precision (inter-day < 0.599%, intra-day < 0.055%), and accuracy (recoveries 92.30–108.80%). The HPLC–DAD method was subsequently applied to analyze flavonoids in Citrus samples. Overall, the quantification results indicated that the compositions and content of flavonoids differed for each Citrus species. The harvesting period also influenced the changes in flavonoid content within each Citrus species. The analytical results with chemometrics revealed that higher flavonoid levels in early-harvested Citrus were derived from the improved fruit size and reduced flavonoid synthesis during maturation. This study provides a practical and reliable method for the analysis of ten flavonoids that can be further utilized in the quality assessment of Jeju Citrus.